2019
DOI: 10.1001/jamanetworkopen.2019.2514
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Cigarette Smoking and Smoking Cessation With Preterm Birth

Abstract: IMPORTANCE Cigarette smoking during pregnancy increases the risk of preterm birth, low birth weight, and infant mortality. OBJECTIVE To assess the probability of preterm birth among expectant mothers who smoked cigarettes before pregnancy and quit smoking at the start or during pregnancy. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study analyzed information provided on live birth certificates from 2011 through 2017 that were obtained from US states that implemented the 2003 revision of the US live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 34 publications
7
101
1
3
Order By: Relevance
“…There is evidence that smoking cessation after becoming pregnant is associated with a reduced risk of preterm birth [8]. In past research, women who were younger than 20, Asian/Pacific Islander, had more than 12 years of education, had private insurance, and lived in urban areas were most likely to quit smoking during pregnancy [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that smoking cessation after becoming pregnant is associated with a reduced risk of preterm birth [8]. In past research, women who were younger than 20, Asian/Pacific Islander, had more than 12 years of education, had private insurance, and lived in urban areas were most likely to quit smoking during pregnancy [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking is a modifiable environmental factor associated with many adverse pregnancy results, such as low birth weight, preterm birth, and higher newborn mortality [2,4,[6][7][8]. Tobacco smoke contains several thousand chemicals that can be harmful to the placenta and pass through the placenta to the fetus [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO data, the percentage of premature births in Serbia increased from 7.23% in 2000 to 11.97% in 2014 (22). Data from a few studies conducted in Serbia indicated the existence of some of the premature birth risk factors, such as maternal age (23), smoking (24), obesity, and overweight mothers (25). Delayed maternity is often present among women in Serbia, which increases the risk of preterm delivery.…”
Section: Discussionmentioning
confidence: 99%